A method for improving titanium / steel dissimilar metal connection by utilizing a porous high-entropy alloy structure

CN118989872BActive Publication Date: 2026-10-27SHANGHAI UNIV OF ENG SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411147956.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2026-10-27
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

[0005]目前尚无将高熵合金与激光选区熔化技术结合来解决钛和钢连接问题的方法

Benefits of technology

[0022]按本发明方法所制备的多孔高熵合金结构致密且牢固,成形良好,具有较高的强度和塑性,基板背面、侧面无宏观变形;有多孔高熵合金中间层的情况下,激光填丝焊接焊缝成形连续且均匀,无裂纹生成,有效解决了直接在钢板上进行钛丝填丝焊接所产生的焊缝表面氧化严重、有多处明显的裂纹甚至出现焊缝与基板剥离的问题。与现有技术相比,本发明多孔高熵合金中间层的加入,使得钛/钢异质金属形成了高可靠性连接。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118989872B_ABST
    Figure CN118989872B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of laser welding, and specifically discloses a method for improving titanium / steel heterogeneous metal connection by using a porous high-entropy alloy structure, which takes gas-atomized FeCoCrNiMn high-entropy alloy powder as raw material, forms a three-dimensional porous high-entropy alloy structure on a steel plate by using a laser selective melting process, and then performs titanium wire filling welding on the porous high-entropy alloy structure. The porous high-entropy alloy structure prepared by the application is dense and firm, has good forming, high strength and plasticity, and no deformation on the back and side of the substrate; under the condition of the porous high-entropy alloy intermediate layer, the laser wire filling welding seam is continuously and uniformly formed without crack generation, thereby solving the problem that titanium / steel heterogeneous metals cannot be effectively connected due to large differences in physical and chemical properties, and effectively improving the utilization rate and productivity of titanium / steel material connection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser welding technology, and more specifically to a method for improving the joining of titanium / steel dissimilar metals using a porous high-entropy alloy structure. Background Technology

[0002] Titanium possesses advantages such as high specific strength, corrosion resistance, and high temperature resistance, but its widespread application is limited by high manufacturing costs. Steel, on the other hand, is the most widely used traditional structural material, offering advantages such as low manufacturing costs and excellent mechanical properties. High-reliability joining of titanium / steel dissimilar materials can fully leverage the complementary performance and economic advantages of both materials, showing broad application prospects in many fields such as aerospace, energy and chemical engineering, marine equipment, and medical devices. However, titanium and steel differ significantly in properties such as melting point, thermal conductivity, and coefficient of thermal expansion. During welding, uneven heating and internal stress can easily occur, reducing joint quality. Furthermore, brittle intermetallic compounds are easily formed in the joint, leading to cracking and making it difficult to form a reliable connection.

[0003] High-entropy alloys (HEAs) typically consist of at least five principal elements in equimolar ratios and have attracted widespread attention due to their simple crystal structure and complex composition. Their high mixing entropy and multiple principal elements generate a high-entropy effect, inhibiting the formation of intermetallic compounds. Furthermore, the varying sizes and bonding forces between elements lead to lattice distortion and slow diffusion effects. In addition, the "cocktail" effect in their properties typically results in high strength, high-temperature thermal stability, and high corrosion resistance simultaneously. Due to these superior properties, HEAs have a wide range of applications, including wear-resistant coatings, aerospace materials, hydrogen storage materials, thermoelectric materials, biomedical materials, nuclear structural materials, superconducting materials, and electromagnetic materials.

[0004] Selective Laser Melting (SLM) is an additive manufacturing (3D printing) technology that uses a high-power laser to melt and solidify metal powder layer by layer, ultimately forming complex metal parts. SLM technology can produce highly complex and intricate structures with extremely high material utilization. Because the sample can cool rapidly during the SLM process, resulting in refined grain structures, the manufactured metal parts typically possess high strength and hardness, among other mechanical properties. These advantages make SLM one of the most widely used additive manufacturing technologies.

[0005] Currently, there is no method to combine high-entropy alloys with selective laser melting technology to solve the problem of joining titanium and steel. Summary of the Invention

[0006] To address the challenge of effectively joining dissimilar titanium and steel, this invention proposes a method for improving the connection of titanium and steel dissimilar metals using a porous high-entropy alloy structure. The porous high-entropy alloy structure is prepared using selective laser melting (SLM) technology as an intermediate layer, achieving a highly reliable connection between titanium and steel dissimilar metals.

[0007] To achieve the above objectives, the specific technical solution adopted by the present invention is as follows:

[0008] A method for improving the bonding of titanium / steel dissimilar metals using a porous high-entropy alloy structure involves using atomized FeCoCrNiMn high-entropy alloy powder as raw material and employing a laser selective melting process to form a three-dimensional porous high-entropy alloy structure between titanium and steel. This three-dimensional porous high-entropy alloy structure is a hollow, three-dimensional structure with two parallel, uniformly distributed mesh surfaces containing through-holes. This hollow, three-dimensional porous high-entropy alloy structure ensures that the welding wire, after melting, can fully wet and spread during titanium wire filler welding, achieving better bonding between the interfaces.

[0009] More specifically, the method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures includes the following steps:

[0010] S1. Using a steel plate as a substrate, sand it with sandpaper to remove the surface oxide film, clean and wipe it, and finally dry it for later use;

[0011] S2. The raw materials were weighed and proportioned according to the molar ratio of each element in the chemical composition of the high-entropy alloy, and FeCoCrNiMn high-entropy alloy powder was prepared by vacuum atomization method.

[0012] S3. Use 3D modeling software to draw a porous high-entropy alloy structure, slice the 3D model, set the thickness of each slice according to the height of the structure, convert it into a CLS format file and import it into the metal powder rapid prototyping system.

[0013] S4. Place the high-entropy alloy powder obtained in S2 into the metal powder rapid prototyping system equipment in S3, clamp the substrate in S1 with the fixture and install it in the laser action area, set various process parameters, melt and solidify the high-entropy alloy powder to obtain a porous high-entropy alloy structural part.

[0014] S5. Using a semiconductor laser to perform titanium wire filler welding on a porous high-entropy alloy structure to form an effective connection between titanium and steel dissimilar metals.

[0015] Preferably, in step S2, the particle size of the high-entropy alloy powder is in the range of 15–50 μm. Powder within this range can provide better printing accuracy and surface finish, facilitate better spreading, and absorb laser energy more quickly, thereby melting faster and improving the density and strength of the finished product. However, excessively small particle sizes may result in poor flowability, making uniform spreading difficult and affecting the forming effect; excessively large particle sizes can easily create large pores in the printed layer, leading to reduced density and deterioration of mechanical properties in the finished product. The high-entropy alloy powder has the following composition by mass percentage: Fe: 19.98%; Co: 21.06%; Cr: 18.24%; Ni: 21.03%; Mn: 19.69%.

[0016] As a preferred option, the main process parameters used in step S4 for the laser selective melting structure forming process are: spot diameter 50μm, laser power 90~120W, scanning speed 800~1100mm / s, and powder thickness per pass 0.02mm.

[0017] Preferably, in step S4, the high-entropy alloy structure forming process involves introducing an inert gas with a purity greater than 99.9% into the printing chamber and heating it to 125°C. Temperatures that are too high or too low may result in an undesirable structure, further affecting subsequent forming processes. Excessive temperature leads to grain coarsening, easily forming brittle or unfavorable phase transitions, resulting in decreased mechanical properties; insufficient temperature results in incomplete powder heating, easily causing unmelted powder, high particle size, and consequently poor interfacial bonding. Furthermore, the inert gas introduced is pure argon.

[0018] As a preferred option, in step S5, the main process parameters for laser wire filler welding are: spot diameter 50μm, laser power 900~1100W, welding speed 3~4mm / s, wire feed speed 90~110cm / min, and defocusing amount 0mm.

[0019] Preferably, in step S5, an inert gas is introduced during the welding process at a flow rate of 20–30 L / min to isolate the front and sides of the welding wire from the air during welding. If the gas flow rate is less than 20 L / min, it cannot effectively protect the weld; if it is greater than 30 L / min, it will affect the surface quality of the weld and reduce its strength. Furthermore, the inert gas introduced is pure argon.

[0020] Preferably, both the substrate and the fixture are made of 316L steel.

[0021] The present invention has the following beneficial effects:

[0022] The porous high-entropy alloy structure prepared by the method of this invention is dense and robust, well-formed, and possesses high strength and plasticity, with no macroscopic deformation on the back and sides of the substrate. With the presence of a porous high-entropy alloy interlayer, the laser-welded weld seam is continuous and uniform, without crack formation, effectively solving the problems of severe surface oxidation, numerous obvious cracks, and even weld seam delamination from the substrate that occur when directly welding titanium wire onto steel plates. Compared with existing technologies, the addition of the porous high-entropy alloy interlayer in this invention enables a highly reliable connection between titanium and steel dissimilar metals. Attached Figure Description

[0023] Figure 1 : A schematic diagram of the fixture designed in Example 1. In the figure, 1-counterhead, 2-groove, 3-threaded hole.

[0024] Figure 2 : A three-dimensional diagram of the porous high-entropy alloy structure drawn in Example 1.

[0025] Figure 3 The porous high-entropy alloy structure printed by the metal powder rapid prototyping system in Example 1; wherein, Figure a shows the macroscopic morphology from the front, and Figures b and c show the microscopic morphology of the structure formed under confocal conditions.

[0026] Figure 4 : Schematic diagram of the connection of the intermediate layer of the porous high-entropy alloy structure in Example 1, and the titanium wire laser filler wire welding joint.

[0027] Figure 5 In Example 1, 316L is used as the substrate, a porous high-entropy alloy structure is used as the intermediate layer, and the macroscopic morphology is obtained by titanium wire laser filler welding.

[0028] Figure 6 Comparative Example 1 shows the morphology of titanium wire laser filler welding performed directly on a 316L substrate. Figure a shows a schematic diagram of the titanium wire laser filler welding joint connection, figure b shows the macroscopic crack morphology of the weld, and figure c shows the macroscopic peeling morphology of the weld. Detailed Implementation

[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0030] Example 1

[0031] In this embodiment, a porous high-entropy alloy structure is added as an intermediate layer, followed by titanium wire laser filler welding. The specific steps are as follows:

[0032] (1) Draw CAD drawings and, based on the requirements for fit and tolerance, manufacture a 316L substrate fixture with high positioning accuracy and strong clamping force using milling, drilling, and other processes. The fixture structure in this embodiment is as follows: Figure 1As shown, it includes four countersunk holes 1 for fixing the fixture to the printing chamber, a 4mm deep groove 2 for inserting the substrate, and a threaded hole 3 in the groove 2 for fixing the substrate.

[0033] (2) The substrate is a 316L board with dimensions of 150mm (length) × 150mm (width) × 4mm (height). The substrate surface is drilled with holes to fit with the threaded holes 3 in the fixture. It can be fixed by tightening the nuts. The substrate is polished with 200#, 400# and 800# sandpaper in sequence to remove the oxide film on its surface. It is then repeatedly cleaned and wiped with alcohol cotton balls, and finally dried for later use.

[0034] (3) The raw materials were weighed and proportioned according to the molar ratio of each element in the chemical composition of the high-entropy alloy. The FeCoCrNiMn high-entropy alloy powder with high purity, low oxygen content, uniform composition and good sphericity was prepared by vacuum atomization method. The particle size of the high-entropy alloy powder was in the range of 15 to 50 μm, and its composition according to the mass percentage content was as follows: Fe: 19.98%; Co: 21.06%; Cr: 18.24%; Ni: 21.03%; Mn: 19.69%.

[0035] (4) Figure 2 As shown, a porous high-entropy alloy structure is drawn using 3D modeling software. In this embodiment, the porous high-entropy alloy structure is a hollow, flat, elongated cuboid structure with mesh-like surfaces on the top and bottom, and through holes evenly distributed on each surface. The 3D model is sliced, and the thickness of each slice is printed according to the structural height. The slices are then converted into CLS format files and imported into a metal powder rapid prototyping system.

[0036] (5) Place the high-entropy alloy powder obtained in (3) into the metal powder rapid prototyping system equipment in (4), and clamp the substrate in (2) with the fixture in (1) to the laser action area; set the following process parameters: spot diameter 50μm, laser power 100W, scanning speed 1000mm / s, and powder thickness per pass 0.02mm; introduce pure argon gas with a purity greater than 99.9% into the printing chamber and heat it to 125℃, then melt and solidify the high-entropy alloy powder to obtain a porous high-entropy alloy structural part, such as Figure 3 As shown, the prepared porous high-entropy alloy structure is dense and robust, and has good shape.

[0037] (6) Using a semiconductor laser to perform titanium wire filler welding on a porous high-entropy alloy structure (see schematic diagram of the welding joint connection). Figure 4As shown, the main process parameters for laser wire filler welding are: spot diameter 50μm, laser power 1100W, welding speed 3mm / s, wire feed speed 100cm / min, defocusing amount 0mm; pure argon gas is introduced during the welding process, with a gas flow rate of 25L / min, to isolate the front and sides of the welding wire from the air during the welding process.

[0038] like Figure 5 As shown, in this embodiment, with a porous high-entropy alloy intermediate layer, the laser filler wire welding weld is continuous and uniform, with slight oxidation and no crack formation.

[0039] Comparative Example 1

[0040] This comparative example uses a non-porous high-entropy alloy structure, where titanium wire is directly welded onto a steel plate. The specific steps are as follows:

[0041] (1) Polish the 316L substrate with 200#, 400# and 800# sandpaper in sequence to remove the oxide film on its surface, and clean and wipe it repeatedly with alcohol cotton balls, and finally dry it for later use.

[0042] (2) Assemble and fix the processed 316L substrate.

[0043] (3) Titanium wire filler welding was performed on the steel plate using a semiconductor laser. The main process parameters for laser filler welding were: spot diameter 50μm, laser power 1100W, welding speed 3mm / s, wire feed speed 100cm / min, and defocusing amount 0mm. Pure argon gas was introduced at a flow rate of 25L / min during the welding process to isolate the front side of the welding area of ​​the plate to be welded from the air.

[0044] like Figure 6 As shown, the weld surface is severely oxidized, with multiple obvious cracks, and even instances of weld separation from the substrate. Microscopic examination of the weld cross-section reveals several obvious cracks.

[0045] Comparative Example 2

[0046] This comparative example uses a sintering method to prepare a porous high-entropy alloy intermediate layer from Example 1, which is used for joining dissimilar metals such as titanium and steel.

[0047] Experiments have shown that sintering typically requires high temperatures (around 1200℃) and complex equipment, increasing process complexity and production costs. For high-entropy alloys, controlling the temperature and time during sintering is particularly critical; even slight errors can lead to material degradation. Furthermore, during high-temperature sintering, high-entropy alloy powder may react with oxygen in the air, causing oxidation and consequently affecting coating performance.

[0048] In contrast, the porous high-entropy alloy interlayer structure prepared by selective laser melting has no redox reaction, good forming effect, strong bonding performance, and simple process and preparation.

[0049] In summary, the method of using selective laser melting to prepare porous high-entropy alloy interlayer structures for titanium / steel dissimilar metal bonding is superior.

[0050] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. Any changes made by those skilled in the art after reading the specification of the present invention, as long as they are within the scope of the claims of the present invention, will be protected by patent law.

Claims

1. A method for improving titanium / steel dissimilar metal connections using porous high-entropy alloy structures, characterized in that, Using atomized FeCoCrNiMn high-entropy alloy powder as raw material, a three-dimensional porous high-entropy alloy structure is formed between titanium and steel using a laser selective melting process. The three-dimensional porous high-entropy alloy structure is a hollow three-dimensional structure with two parallel, uniformly distributed mesh surfaces containing through-holes. The method includes the following steps: S1. Using a steel plate as a substrate, sand it with sandpaper to remove the surface oxide film, clean and wipe it, and finally dry it for later use; S2. The raw materials were weighed and proportioned according to the molar ratio of each element in the chemical composition of the high-entropy alloy, and FeCoCrNiMn high-entropy alloy powder was prepared by vacuum atomization method. S3. Use 3D modeling software to draw a porous high-entropy alloy structure, slice the 3D model, set the thickness of each slice according to the height of the structure, convert it into a CLS format file and import it into a metal powder rapid prototyping system. S4. The high-entropy alloy powder obtained in S2 is placed into the metal powder rapid prototyping system equipment in S3. The substrate in S1 is clamped and installed in the laser action area with the fixture. After setting various process parameters, the high-entropy alloy powder is melted and solidified to form a porous high-entropy alloy structure. S5. Using a semiconductor laser to perform titanium wire filler welding on a porous high-entropy alloy structure to form an effective connection between titanium and steel dissimilar metals.

2. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 1, characterized in that: In step S2, the high-entropy alloy powder has a particle size range of 15-50 μm, and its composition by mass percentage is as follows: Fe: 19.98%; Co: 21.06%; Cr: 18.24%; Ni: 21.03%; Mn: 19.69%.

3. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 1, characterized in that: In step S4, the main process parameters used in the laser selective melting structure forming process are: spot diameter 50μm, laser power 90~120W, scanning speed 800~1100mm / s, and powder thickness per pass 0.02mm.

4. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 1, characterized in that: In step S4, the high-entropy alloy structure forming process involves introducing an inert gas with a purity greater than 99.9% into the printing chamber and heating it to 125°C.

5. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 4, characterized in that: In step S4, the inert gas used is pure argon.

6. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 1, characterized in that: In step S5, the main process parameters for laser wire filler welding are: spot diameter 50μm, laser power 900~1100W, welding speed 3~4mm / s, wire feed speed 90~110cm / min, and defocusing amount 0mm.

7. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 1, characterized in that: In step S5, an inert gas is introduced during the welding process at a flow rate of 20-30 L / min to isolate the front and sides of the welding wire from the air during the welding process.

8. The method for improving titanium / steel heterometallic connections using porous high-entropy alloy structures according to claim 7, characterized in that: In step S5, the inert gas used is pure argon.

Citation Information

Patent Citations

  • High entropy alloy material for welding and application

    CN109955004A